Design, Fabrication, and Performance Evaluation of Electric Motor Driven Cassava (Manihot esculenta) Grater with Juice Extractor (Philippine Journal of Agricultural Economics, 2017)
Modern agriculture requires a modern approach which responds to the necessity of mankind. The study presents the fabrication and performance evaluation of a cassava grater with  juice extractor. Such performance evaluation was conducted to determine its grating and juice extracting capacity and efficiency. It was made from locally available materials then tested experimentally using cassava with a grating capacity of 160 kg/hr. The study employed the Complete Randomized Experimental Design (CRD). In evaluating the experiment, the Two-way Analysis of Variance (ANOVA) was used to determine the significant effect of each factor and the Tukey's test was used to determine the significant difference between the combined treatments. Two factors with different levels were treated upon the experiment.  These were mainly soaking time (0 min, 5 min, 10 min, 15 min) and the way the cassava was grated and juice extracted (Machine, Manual).  Among these treatment combinations, the soaking time of 15 minutes obtained the highest grating and extracting capacity as well as for the grating and extracting efficiency leaving its quality and acceptable appearance on top.  The computed benefit-cost ratio of 1.86 showed that grating and extracting cassava juice using the cassava grater with juice extractor was highly profitable and economical for local cassava producers.